Immunohistochemical staining pattern of epidermal growth factor receptor (EGFR) protein overexpression in non-small cell lung cancer / Muhamad Asri Abd Rahman - Abd Rahman, Muhamad Asri (2012)
Lung cancer is the leading cause of cancer death worldwide and non-small cell lung cancer (NSCLC) accounts for almost 80% of such deaths. Non-small cell lung cancer (NSCLC) is considered as a heterogeneous disease; where patients with similar clinical and pathologic features show different outcomes: some are cured, whereas in others, the cancer recurs. Hence, some patients may receive potentially toxic chemotherapy unnecessarily. The discovery of the epidermal growth factor receptor (EGFR) signaling pathway as a therapeutic target leads to the development of small molecule tyrosine kinase inhibitors (TKIs). However, EGFR protein overexpression in NSCLC varies in previous studies with some contradicting results. The aim of this study is to determine the expression pattern (membranous vs. cytoplasmic) and heterogeneity (percentage of positive tumour cells) of EGFR immunohistochemical staining in adenocarcinoma type of non small cell lung carcinoma. The samples were formalin-fixed and paraffin-embedded tissue.